Coronally advanced flap with and without connective tissue graft for the treatment of multiple gingival recessions: a comparative short‐ and long‐term controlled randomized clinical trial. (22nd January 2014) - Zucchelli, Giovanni; Mounssif, Ilham; Mazzotti, Claudio; Stefanini, Martina; Marzadori, Matteo; Petracci, Elisabetta; Montebugnoli, Lucio
Abstract Aim The aim of this study was to compare short‐ and long‐term root coverage and aesthetic outcomes of the coronally advanced flap (CAF) alone or in combination with a connective tissue graft (CTG) for the treatment of multiple gingival recessions. Methods Fifty patients with multiple (≥2) adjacent gingival recessions (≥2 mm) in the upper jaw were enrolled. Twenty‐five patients were randomly assigned to the control group (CAF), and the other 25 patients to the test group (CAF + CTG). Clinical outcomes were evaluated at 6 months, 1 and 5 years. The aesthetic evaluations were made 1 and 5 years after the surgery. Results No statistically significant difference was demonstrated between the two groups in terms of Rec Red and complete root coverage (CRC) at 6 months and 1 year. At 5 years, statistically greater recession reduction and probability of CRC, greater increase in buccal KTH and better contour evaluation made by an independent periodontist were observed in the CAF + CTG group. Better post‐operative course and better colour match were demonstrated in CAF‐treated patients both at 1 and 5 years. Conclusions CAF + CTG provided better CRC at 5 years; keloid formation due to graft exposure was responsible for the worse colour match evaluation.